(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Benzylphenol has been produced in high yield by the benzylation of phenol with benzyl alcohol in the presence of sulphuric acid. The effect of variation of temperature, molar ratio of phenol to benzyl alcohol, time of reaction, concentration and amount of sulphuric acid have been studied on the reaction. Bangladesh J. Sci. Ind. Res. 41(3-4), 257-261, 2006